Efficacy and Safety of Oral Creatine Supplementation in Patients with Heart Failure: A PRISMA 2020 Systematic Review and Narrative Evidence Synthesis - Francisco Epelde; María Pilar Martínez López (International Journal of Environmental Research and Public Health, 2026)
Background: Oral creatine is biologically plausible as an adjunct in heart failure (HF), but its clinical efficacy and safety remain uncertain. Methods: We performed a PRISMA 2020 systematic review (PROSPERO CRD420261391605) of oral creatine supplementation in adults with HF. Randomized parallel-group and crossover trials formed the primary causal evidence base; non-randomized HF evidence was analyzed separately. Risk of bias was assessed with RoB 2 and certainty with GRADE. Results: Four randomized HF-only trials were identified as primary evidence, with one additional open-label HF study retained as exploratory evidence. Because studies differed in dose, duration, outcome definitions, measurement scales, crossover structure, and availability of variance data, meta-analysis was not considered defensible. Randomized evidence showed no consistent benefit for peak VO2, 6-min walk distance, quality of life, or cardiac systolic function. A preliminary signal was observed for selected peripheral muscle and muscle-energetic outcomes. Safety reporting was sparse and insufficient to establish long-term renal or clinical safety. Certainty was very low across critical outcomes. Conclusions: Current evidence does not support routine oral creatine supplementation in HF. Larger contemporary placebo-controlled trials with systematic safety surveillance are required.